The Role of Social Media in Promoting Tourism in Bangli Regency - Ni Wayan Sumariadhi (Samā Jiva Jnānam (International Journal of Social Studies), 2023)
This study aimed to find out the role of social media in promoting tourism attraction in Bangli regency, specifically. Social media has been a part of human daily life nowadays. It includes all the need of human to have including the need of travelling in many tourism objects and social media can provide all the information if someone wants to go travelling immediately. The study used literature study to collect the data from many sources especially in online form. This study found out that the role of social media has 3 roles. Firstly, the role of information dissemination and accessibility. Secondly, the role of engagement and interaction among users. Lastly, the role of trendsetting and virality. The study implied that the use of social media must be maximized to get better interaction between the tourism objects and the tourist and it is also expected that the role of social media can be one of the solutions to promote all the attraction.